(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the role of phraseological units in the linguistic system, focusing on the comparison of phraseological expressions in Uzbek and English. It highlights the formation of synonymous expressions through various components, either somatic or other types, in these two languages. Somatic phraseological units serve as the basis for the comparison. Examples are provided to support the argument.